To determine the similarity between the two triangles, we first need to find the missing angles in both triangles.
For triangle \(ABC\):
- Given: \(m\angle A = 47^\circ\) and \(m\angle B = 36^\circ\).
- The sum of angles in a triangle is \(180^\circ\): \[ m\angle C = 180^\circ - m\angle A - m\angle B = 180^\circ - 47^\circ - 36^\circ = 97^\circ. \]
For triangle \(GHJ\):
- Given: \(m\angle G = 36^\circ\) and \(m\angle J = 97^\circ\).
- Calculate the missing angle \(H\): \[ m\angle H = 180^\circ - m\angle G - m\angle J = 180^\circ - 36^\circ - 97^\circ = 47^\circ. \]
Now we have:
- Triangle \(ABC\) has angles: \(47^\circ, 36^\circ, 97^\circ\).
- Triangle \(GHJ\) has angles: \(36^\circ, 47^\circ, 97^\circ\).
Since both triangles have the same angles, we can conclude:
\[ \triangle ABC \sim \triangle GHJ. \]
Thus, the appropriate response is:
\[ \triangle ABC \sim \triangle GHJ. \]